Pergulatan Internasionalisasi Konsep Hak Asasi Manusia Proses Globalisasi dan Implikasinya Terhadap Penegakan Hukum di Indonesia: Menciptakan Konsep Hak Asasi Manusia Elusif? - Susanti, Liana Endah; Gumbira, Seno Wibowo (Fakultas Syariah INSURI Ponorogo, 2023)
This article discusses the elusive development of the concept of Human Rights in Indonesia, as evident through the frequent emergence of anarchic actions carried out under the banner of Human Rights. The primary issues addressed are why the substance of constitutional law and Human Rights is considered elusive, and how to categorize actions that manifest an elusive aspect of Human Rights. In order to elucidate this phenomenon, the author employs a normative juridical approach and draws upon various secondary sources from relevant literature. It is hoped that this study can shed light on the social climate in Indonesia. There are several factors influencing the elusiveness of constitutional substance and Human Rights. One of the most prominent factors is the performance of law enforcement influenced by system, structure, substance, and culture. Additionally, an excessive sentiment in legal violations, cultural and social differences conflicting with the nation's ideology, social behaviors driven by socio-political issues, and a lack of understanding of Human Rights and constitutional substance all contribute to this complexity. This article aims to delineate these issues and provide a clearer insight into the challenges faced in upholding Human Rights in Indonesia.